1 \documentclass[12pt
]{article
}
6 E & = &
\frac{1}{2} \sum_i \sum_{j
\neq i
} V_
{ij
} \\
7 V_
{ij
} & = & f_C(r_
{ij
})
\left[ f_R(r_
{ij
}) + b_
{ij
} f_A(r_
{ij
})
\right] \\
8 f_C(r) & = &
\left\
{ \begin{array
} {r@
{\quad:
\quad}l
}
10 \frac{1}{2} -
\frac{9}{16} \sin \left(
\frac{\pi}{2} \frac{r-R
}{D
} \right) -
\frac{1}{16} \sin \left(
\frac{3\pi}{2} \frac{r-R
}{D
} \right) &
13 \end{array
} \right. \\
14 f_R(r) & = & A
\exp (-
\lambda_1 r) \\
15 f_A(r) & = & -B
\exp (-
\lambda_2 r) \\
16 b_
{ij
} & = &
\left(
1 +
{\zeta_{ij
}}^
\eta \right)^
{-
\frac{1}{2n
}} \\
17 \zeta_{ij
} & = &
\sum_{k
\neq i,j
} f_C(r_
{ik
}) g(
\theta_{ijk
})
18 \exp \left[ \alpha (r_
{ij
} - r_
{ik
})^
\beta \right] \\
19 g(
\theta) & = & c_1 + g_o(
\theta) g_a(
\theta) \\
20 g_o(
\theta) & = &
\frac{c_2 (h -
\cos \theta)^
2}{c_3 + (h -
\cos \theta)^
2} \\
21 g_a(
\theta) & = &
1 + c_4
\exp \left[ -c_5 (h -
\cos \theta)^
2 \right] \\